Differential coping strategies exerted by biofilm and planktonic cells of the beneficial bacterium B. subtilis in response to the protozoan predator Entamoeba histolytica - Kolodkin-Gal, Ilana; Prem Anand Murugan; Zanditenas, Eva; Ankri, Serge (bioRxiv, 2024)
The human protozoan parasite Entamoeba histolytica causes amebiasis and interacts with both beneficial and harmful members of the microbiome. In previous studies, it was shown that E. histolytica can break down pre-established biofilms of B. subtilis in a time- and dose-dependent manner. Inhibiting parasitic cysteine proteases impairs biofilm degradation. However, it is still unknown whether bacteria can sense this process and respond to the degradation of the biofilms. Here, our research demonstrates a multi-layered response of probiotic bacteria to the parasite, which differs between planktonic bacteria and pre-established biofilms. Sensing the activity of cysteine proteases from E. histolytica, the bacteria activate the general stress response and, to a lesser extent, the cell wall stress response, making the surviving biofilm members more resistant to mild stressors. On the other hand, planktonic cells exposed to the predators' lysate deactivate the expression of genes associated with biofilm formation while inducing their motility to avoid predation. Overall, our results indicate that bacteria have evolved to recognize amoeba predators. Furthermore, the partially digested biofilm cells may have unexpected disadvantages over bacteria that did not encounter a predator. These findings may be useful in developing more efficient probiotic strains that are resilient to amoebiasis.Competing Interest StatementThe authors have declared no competing interest.